Design and performance of a Martian autonomous navigation system based on a smallsat constellation. (February 2023) - Molli, S.; Durante, D.; Boscagli, G.; Cascioli, G.; Racioppa, P.; Alessi, E.M.; Simonetti, S.; Vigna, L.; Iess, L.
Abstract: Deciphering the genesis and evolution of the Martian polar caps can provide crucial understanding of Mars' climate system and will be a big step forward for comparative climatology of the terrestrial planets. The growing scientific interest for the exploration of Mars at high latitudes, together with the need of minimizing the resources onboard landers and rovers, motivates the need for an adequate navigation support from orbit. In the context of the ARES4SC study, we propose a novel concept based on a constellation that can support autonomous navigation of different kind of users devoted to scientific investigations of those regions. We study two constellations, that differ mainly for the semi-major axis and the inclination of the orbits, composed of 5 small satellites (based on the SmallSats design being developed in Argotec), offering dedicated coverage of the Mars polar regions. We focus on the architecture of the inter-satellite links (ISL), the key elements providing both ephemerides and time synchronization for the broadcasting of the navigation message. Our concept is based on suitably configured coherent links, able to suppress the adverse effects of on-board clock instabilities and to provide excellent range-rate accuracies between the constellation's nodes. The data quality allows attaining good positioning performance for both constellations with a largely autonomous system. Indeed, we show that ground support can be heavily reduced by employing an ISL communication architecture. Periodic synchronization of the clocks on-board the constellation nodes with terrestrial time (TT) is enabled through the main spacecraft (the mother-craft ), the only element of the constellation enabling radio communication with the Earth. We report on the results of numerical simulations in different operational scenarios and show that a very high-quality orbit reconstruction can be obtained for the constellation nodes using a batch-sequential filter or a batch filter with overlapping arcs, that could be implemented on board the mother-craft, thus enabling a high level of navigation autonomy. The assessment of the achievable positioning accuracy with this concept is fundamental to evaluate the feasibility of a future positioning system providing a global coverage of the red planet. Highlights: Polar constellation of small satellites on Mars. Provide navigation services for Martian landers, rovers, and orbiters. Quasi-autonomous constellation ephemeris reconstruction. Novel tracking technique for inter-satellite link.